PENGARUH PEMANASAN BAHAN BAKAR MELALUI 2 PIPA TEMBAGA BERSIRIP RADIAL PADA UPPER TANK RADIATOR DAN PENAMBAHAN ETANOL PADA BAHAN BAKAR TERHADAP EMISI GAS BUANG MOBIL SUZUKI APV - Ihsan Firdaus; Danar Susilo Wijayanto; Husin Bugis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
This research aims to : 1) Investigate the effect of heating fuel through radial finned copper pipe in the upper tank of the radiator exhaust emissions on cars Suzuki APV; 2) Investigate the effect of adding ethanol to the fuel pertalite against exhaust emissions on cars Suzuki APV; 3) Investigate the effect of heating fuel through radial finned copper pipe in the upper tank of the radiator and the addition of ethanol to the fuel pertalite against exhaust emissions on cars Suzuki APV; 4) Analyze the comparison between the results of the fuel mixture pertalite heating and heating fuel ethanol pertamax through two copper pipe to the exhaust emissions of the Suzuki APV. This research use you right experimental method with a comparative descriptive data analysis. The sample used is a Suzuki APV with G15A1D100006 machine number. Data were obtained from a large measurement exhaust emission levels CO and HC for 20 seconds at idle rotation with variations mix pertalite and ethanol as much as 0%, 5%, 10%, 15%, 20%, 25%, and 30% using the method without heating fuel and the use of heating fuel through a copper pipe finned radial variation fin spacing of 10 mm, 20 mm and 30 mm In the upper radiator tank. Data obtained from the research that is inserted into the table and displayed in a graph, and then analyzed. The results of this study were: 1) heating fuel pertalite in radial finned pipe through the upper radiator tank to the injection cars Suzuki APV can decrease the value of exhaust emissions of CO and HC;2) Addition of ethanol in fuel pertalite with higher levels of 0% to 20% decline in the value of exhaust emissions of CO and HC. Exhaust emissions of CO and HC to increase again in the levels of ethanolblending with levels of 25% and 30%; 3) heating fuel in a radial finned pipe through the upper radiator tank to the injection Suzuki APV car down the value of exhaust emissions of CO and HC. Value exhaust emissions lowest CO occur in the application of finned pipe distance of 10 mm with a mixture of 20% ethanol content of 19% and HC 0.3 by 2 24 to 33 ppm; 4) The value of exhaust emissions of CO and HC in blending ethanol content to 20% lower than the lowest value of the results of exhaust emissions of CO and HC pertamax pure with a value of 0.354% levels of CO and HC at 229.67 Ppm.